Choriocarcinoma with multiple lung metastases from complete hydatidiform mole with coexistent fetus during pregnancy. Issue 8 (29th May 2018) - Maeda, Yuto; Oyama, Ruriko; Maeda, Hirona; Imai, Yukihiro; Yoshioka, Shinya
Abstract: Gestational trophoblastic neoplasm (GTN) is a serious morbidity of complete hydatidiform mole with coexistent fetus (CHMCF) and usually develops after termination of pregnancy. Here we report a case of choriocarcinoma derived from CHMCF during pregnancy. A 33‐year‐old multiparous woman with suspected CHMCF was admitted with a severe cough. Computed tomography revealed multiple lung metastases. Cesarean section and hysterectomy were performed at 31 weeks of gestation on diagnosis of high‐risk GTN from International Federation of Gynecology and Obstetrics (FIGO) scoring. A live female infant weighing 1390 g was delivered. Choriocarcinoma was diagnosed from pathological findings. The patient received multi‐agent chemotherapy and was discharged on the 40th postoperative day. In conclusion, CHMCF can result in high‐risk GTN during pregnancy. For a suspected GTN, diagnosis from FIGO scoring should determine treatment strategy. If patients with CHMCF wish to continue their pregnancy, careful follow‐up, including regular chest radiography and ultrasonography, is warranted.